COOPERATION BETWEEN INDONESIA AND MOZAMBIQUE THROUGH THE INDONESIA-MOZAMBIQUE PREFERENTIAL TRADE AGREEMENT (IM-PTA) IN 2019 - Rafii Putra Bakti; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Indonesia is a country that has a high rate of economic growth. In supporting its economic growth, Indonesia relies on export and import processes. Thus far, Indonesia's export and import markets have always been focused on Asia and Europe. The value of Indonesia's exports and imports to the African continent tends to be small. Indonesia is deemed necessary to undertake a strategy to prevent negative impacts from economic activities, including strong dependencies on its traditional markets.This research is built on the assumptions of the Preferential Trade Agreement theory by referring to the General Agreement on Tariffs and Trade (GATT) rules. The formulation of all arguments, data, facts, and theoretical frameworks in this study using descriptive methods and document analysis. The data absorbed from books, journals, news from newspapers and magazines, and websites. This study shows the reasons why Indonesia chose Mozambique as a preferential trade cooperation partner within the IM-PTA framework. The IM-PTA regulates tariff reduction for Indonesia's main export and import commodities. This tariff reduction is to support the expansion of the Indonesian market to non-traditional partners in the African continent. Mozambique is the first country to have a trade agreement with Indonesia on a bilateral basis. This is also a momentum to start a new non-traditional market for Indonesia.Keywords: IM-PTA, Market diversification, export-import, non-traditional market